2019
DOI: 10.1002/anie.201812529
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of an Early‐Transition‐Metal Alkynyl Cubane Mn4C4 Cluster

Abstract: While the coordination chemistry of monometallic complexes and the surface properties of extended metal particles are well understood, the control of metal nanocluster formation has remained challenging. The isolation of discrete metal clusters provides an especially rare snapshot at the nanoscale of cluster growth. The synthesis and full characterization of the first early-transition-metal alkynyl cubane and the first m 3 -alkynyl Mn 3 motif are reported. Scheme 1. Transition-metal clusters:S carcity of CO-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Thus, these types of complexes are active only for the hydrogenation of polar multiple bonds such as nitriles, imines, and carbonyl compounds, while alkenes are not hydrogenated. In fact, examples of manganese catalysts which are capable of hydrogenating unactivated CC double bonds are exceedingly rare …”
mentioning
confidence: 99%
“…Thus, these types of complexes are active only for the hydrogenation of polar multiple bonds such as nitriles, imines, and carbonyl compounds, while alkenes are not hydrogenated. In fact, examples of manganese catalysts which are capable of hydrogenating unactivated CC double bonds are exceedingly rare …”
mentioning
confidence: 99%
“…Regioselective cyclocarbonylation of 101 to yield either 101a or 101b. Terminally bound CO ligands have been omitted for clarity,[139].Exploring the chemistry of alkyne ligands for polynuclear architectures, Wangelin prepared the first examples of a heteroleptic alkynyl-Mn cubane structure 103, shown in Scheme 31[140]. Based on their previous studies on Fe(N(SiMe3)2) complexes in cyclotrimerization of phenylacetylene 104a to provide either 105a or 105b, cluster 103 was employed as catalyst.…”
mentioning
confidence: 99%
“…Cyclotrimerization of 104a to either 105a or 105b using cubane Mn4-Alkynyl cluster 103 as catalyst. Hmds ligands have been omitted for clarity,[140].Further catalytic studies on 103 found that the cluster is active in the hydrogenation of alkenes, such as α-methylstyrene 1b. Using 1.3 mol% cluster in toluene at 70 °C under 5 bars pressure of H2 for 20 hours resulted in full hydrogenation.…”
mentioning
confidence: 99%
“…In an effort to address the knowledge gap of Fe­(II) pyridonate clusters between the regimes of mononuclear and polynuclear complexes, we set out to explore ligand substitution reactions between the low-valent precursor Fe­(hmds) 2 , iron­(II) bis­(hexamethyldisilazide), and 2-pyridone ligands. Such endeavor complemented our ongoing program of metal-hmds cluster synthesis . Herein, we report the synthesis and characterization of structurally defined heteroleptic N , N , O -ligated Fe­(II) clusters that bear pyridonates in κ 2 ,μ 2 -coordination modes and labile amido ligands (Scheme ).…”
Section: Introductionmentioning
confidence: 99%